Evaluation of the effect of glicerol in the freezing process of canine semen - Herrera, E. (2012)
The main objective of this study was to standardize and evaluate the effect of different glycerol addition proto-ols over the sperm motility and the acrosome morphology after thawing in canine semen. Different concentra-ions of glycerol and different times of Tris-fructose with egg yolk addition were used. Four different protocolsere prepared. Each protocol had two dilution steps. In protocol 1, the first dilution used the extender but nolycerol and the second dilution used the extender plus 7% of glycerol. In protocol 2, both dilutions includedhe extender plus 3.5% of glycerol. In protocol 3, both dilutions used the extender plus 7% of glycerol. In pro-ocol 4, the first dilution used the extender plus 0% of glycerol, while the second dilution used the extenderlus 14% of glycerol. In all the protocols, the first dilution was carried out between 37 and 36°C, the extendedsemen was equilibrated at 7°C for one hour, while the second dilution was carried out at 7°C and subsequentlyquilibrated at 4°C for one hour.A total of 14 dogs of different breeds were selected for the study, which had a satisfactory andrological statusnd their semen presented a minimum of 80% normal morphology and progressive motility. From their ejacula-es, only the second fraction was collected and subsequently divided in 4 equal parts. The semen was packedn straws of 0.5 ml and they were frozen using the manual method. The straws were thawed in a water batht 70°C for 8 seconds, and the motility and acrosome morphology were immediately evaluated using a phaseontrast microscope.Post thawing, the semen showed an average motility of 51.25% (48.57% with protocol 1, 50.71% with protocol, 52.50% with protocol 3 and 53.21% with protocol 4) and the acrosome morphology using a phase contrasticroscope showed a percentage of normal acrosomes of 56.82% with protocol 1, 59.96% with protocol 2,9.18% with protocol 3 and 63.86% with protocol 4.Finally, there were not significant effects (p>0.05) of the time of glycerol addition or the different glycerol con-entrations used, on the percentages of progressive motility and normal acrosome morphology in post-thawedemen samples. Therefore, the canine semen appears to be resistant to the use of different concentrations oflycerol in the extender Tris-fructose with egg yolk. Likewise, the variation of time of glycerol addition did notave any influence on the post-thaw semen quality, in relation to the progressive motility and acrosome integrity.